Purple urine bag syndrome: An unusual but important manifestation of urinary tract infection. Case report and literature review. (January 2019) - Worku, Dominic Adam
Purple urine bag syndrome is a rare albeit alarming purple discolouration of the urine typically seen in elderly ladies with constipation, urinary tract infection and concurrent urinary catheterisation. In this concise review, we report the pathophysiology of this condition and the case of one patient who developed this interesting phenomenon.